Pengaruh Profitabilitas dan Leverage Perusahaan Terhadap Manajemen Laba (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2015-2018) - Brilliant Imani Harlistina; Maslichah Maslichah; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This research was conducted to provide useful information for company management in managing the company's finances and improving the imbalance in the use of profitability and leverage. The purpose of this research is to determine how profitability and leverage affect earnings management. In this research, earnings management is measured using discretionary accruals with the modified Jones model, profitability is measured using Return On Assets (ROA), and leverage is measured using Debt to Asset Ratio (DAR). The population used in this study is all companies in the manufacturing industry sector listed on the Indonesia Stock Exchange (IDX) within the range of 2015-2018, and this research comes from secondary data obtained through purposive sampling method. Based on the calculation data, 10 companies were selected as samples. This research data has met the requirements of the classic assumption test. The results of the analysis using multiple linear regression showed that earnings management has a positive and significant effect on profitability and leverage.Keywords: Profitability, Leverage, Earnings management.